The United Nations and the regulation of cyber-security - Christian Henderson (4466599) (2025)
This chapter reviews the role and activities of the UN in the cyber security context. It argues that while the UN has historically been sluggish in taking on cyber security issues, the UN has, in the wake of the dramatic increase in cyber operations since 2007, gradually begun to address this topic. In particular, activity can be seen in various committees of the UN General Assembly, including the achievement of consensus within several Groups of Governmental Experts on various cyber issues. Additionally, issues of cyber security have surfaced in the UN Security Council, the Economic and Social Council and other subsidiary organs and specialised agencies. This chapter welcomes the decision of these UN agencies to address cyber security, but explains that their next challenge is to cooperate more closely in order to ensure an integrated and concerted response to the maintenance of cyber security.